The Origins of Organized Canadian Medical Research: The National Research Coucil’s Associate Committee on Tuberculosis Research, 1924-1938 - Feldberg, Georgina (Scientia Canadensis, 1991)
AbstractThe National Research Council's Associate Committee on Tuberculosis Research set the standard and precedent for organized Canadian medical research. Established in 1924, the Committee explored some of the most significant biomedical questions of the time, and in 1938 it metamorphosed into the National Research Council's Associate Committee on Medical Research. This circuitous path into medical research elucidates the pragmatic economic, industrial and political concerns that gave the Canadian scientific spirit—or research ideal—shape.